RADIKALISME DALAM TINJAUAN AL-QUR’AN - Syalafiyah, Nurul; Budi Harianto (Bahasa Indonesia, 2024)
Religion in essence teaches people peace and solidarity with eache other, emutual erespect, builds solidaritye bothe withine thee sameereligion and followers of religions outside the religion they profess. However, in our day-to-day, not a few find violenceebyesomeoneewho adheres to aereligion, eboth against theesame religion and to other people whoeadhere eto aedifferent religion. eThe birth ofethe religious radicalism movement is an excess of acts of religion which in turn this understanding creates rigid and extreme people who do not hesitate to behave violently in defending their ideology. Islam is a universal and moderate religion (ummatan wasthan). Islam is also known for teaching the values of tolerance (tasâmuh) which is one of the core teachings of Islam which is parallel to other teachings such as love (mercy), wisdom (wisdom), and justice ('adl). Keyword : Religion, Radicalism, Al-Qur’an, Moderate